Assessment of Somatosensory and Psychosocial Function of Patients With Trigeminal Nerve Damage. Issue 5 (May 2020) - Pillai, Rajath S.; Pigg, Maria; List, Thomas; Karlsson, Pall; Mladenović, Živko; Vase, Lene; Nørholt, Sven E.; Pedersen, Thomas K.; Bengtsson, Martin; Costa, Yuri M.; Svensson, Peter; Baad-Hansen, Lene
Abstract : Objective: The present study assessed somatosensory changes related to trigeminal nerve damage using extensive evaluation tools and assessed the effect of such damage on the patients' psychosocial status and quality of life compared with healthy participants. Methods: In 37 patients with intraorally or extraorally presenting trigeminal nerve damage diagnosed as painful or nonpainful posttraumatic trigeminal neuropathy, psychophysical tests like quantitative sensory testing (QST) and qualitative sensory testing and the electrophysiological "nociceptive-specific" blink reflex were performed. The patients and 20 healthy participants completed a set of questionnaires assessing their psychosocial status and quality of life. Results: A loss or gain of somatosensory function was seen in at least 1 QST parameter in >88.9% of the patients. Patients in whom extraoral QST was performed showed an overall loss of somatosensory function, whereas intraoral QST showed a general gain of somatosensory function. Qualitative sensory testing identified a side-to-side difference in the tactile and pinprick stimulation in >77% of the patients. An abnormal "nociceptive-specific" blink reflex response was seen in 42.1% to 71.4% of patients dependent on the trigeminal branch stimulated, though comparisons with healthy reference values showed ambiguous results. Compared with the healthy participants, patients showed higher scores for pain catastrophizing, symptoms of depression and anxiety, limited jaw function, more somatic symptoms, and significantly impaired oral health-related quality of life (all P <0.038). Discussion: The results from the present study showed presence of varied somatosensory abnormalities when assessed using psychophysical and electrophysiological investigations and a significantly impaired psychosocial status. Abstract : Supplemental Digital Content is available in the text.